Motivations of older Chinese adult learners in Hong Kong - Zhao, Xinyi; Fu, Yuanyuan; Chui, Ernest W.T. (Current Aging Science, 2016)
Background: Motivation for learning, as an important aspect pertaining to studying the phenomenon of elder learning, is not fully explored in Hong Kong. Objective: This study was designed to create a measurement to investigate the possible diversity of motivations of elder learners, so as to harness the older people’s potential in learning and thus capitalize on productive ageing. Methods: 283 older learners participating in learning activities at elder centres were interviewed. Exploratory factor analysis was conducted to identify the latent factors in the learning motivation scale. Reliability of the scale was assessed. ANOVA testing was used to assess for differences in learning motivation by different socio-demographic variables. Results: Four dimensions of older Chinese adults’ motivations for engaging in learning have been found: ‘keeping up with and contributing to society’, ‘fulfilment’, ‘social integration’ and ‘reemployment’. Elders with higher education levels were more likely to seek out opportunities for lifelong learning. Younger (aged 55 to 64) participants of learning activities were more likely than their older (aged 75 or above) counterparts to learn for fulfillment. Older adults who had volunteer experience were more motivated to engage in learning through keeping up with and contributing to society. Conclusion: Older learners in Hong Kong participated in learning for self-fulfilment and development, contributing to society, maintaining social connection, and acquisition of knowledge and qualifications for possible (re)employment. Some of their socio-demographic features might influence their motivations. Learning programmes could be designed and improved based on older adults’ motivations to meet their needs.
Keywords: motivations